Penjaminan Kredit untuk Usaha Kecil Dilihat dari Sistem Hukum - Teuku Ahmad Yani (Universitas Syiah Kuala, 2014)
Credit insurance is an alternative way in ensuring banks to provide credit for a small enterprise. It is not only practiced in European Continental Legal System but also in Anglo Saxon Legal System and Islamic Legal System. In addition viewed from states applying it., it is also applying in Indonesia and Malaysia as developing country and in developed country such as Japan. This research aims to explore the insurance system based on such legal system. Credit Insurance for Small Business Viewed from Legal System